Full‐Color Perovskite Quantum Dots/Cellulose Nanocrystals Enhancement Films with Excellent Stability. Issue 9 (21st September 2021) - Li, Kun-You; Singh, Jitendra; Chiang, Chih-Hao; Liu, Yu-Lun; Chen, Yi-Chen; Li, Ting-You; Tsai, Meng-Lin
Abstract : Cellulose exhibits various interesting aspects like enormous specific surface area, immense tensile durability and stiffness, an abundance of surface hydroxyl groups, biocompatibility, and biodegradability. The green plants in the background of the cover show that the cellulose nanocrystals used in this study are originated from biological sources. The blue, green, and red emitting dots and the paper roll shown in the graph indicate the main feature, perovskite quantum dots/cellulose nanocrystals paper‐like light enhancement films, of the article number 2100424 by Meng‐Lin Tsai and co‐workers.